Providing Ubuntuism Through Participatory Culture Framework: Sustainable Development Goals 4 and 5 - Oluwarotimi Randle (Indonesia Approach Education, 2024)
South Africa is a country of diverse sets of individuals who have different backgrounds and beliefs, there has been a global discussion for the promotion of sustainable development goals, and this paper proposes an approach for the implementation of sustainable development goals 4 and 5 within the South African landscape. (1) The purpose of the research is to discuss the utilization of the African Ubuntu Philosophy through the participatory culture framework for promoting inclusive education. (2) This research was conducted utilizing the 11 components of the Participatory culture framework to practically implement the African Ubuntu Philosophy through the themes defined by Adewale (2023) which included inclusive education, gender sensitization programs, peer support, and mentorship, life orientation curriculum, conflict resolution and restorative justice, student leadership and participation, parent, and community involvement. The utilization of the African Ubuntu Philosophy within a South African University was successful and showed that the approach promoted teamwork and collaboration among the students, it further ensured the provision of leadership roles during classroom activities. The application of the participatory culture framework contributed to the promotion of Sustainable Development Goals 4 and 5 within the classroom environment.